THE RELEVANCE OF ISLAMIC EDUCATION MANAGEMENT PRINCIPLES TO MODERN MANAGEMENT PARADIGMS: A LITERATURE STUDY IN THE CONTEXT OF INDONESIAN EDUCATION - Sofia Nur; Dwi Priyanto; Yulian Purnama (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the relevance of Islamic education management principles to modern management paradigms in the context of Indonesian education, employing a qualitative approach based on systematic literature reviews. Islamic management principles such as amanah, shura, 'adl, and ihsan were found to have a significant contribution in building school leadership that has integrity, participation, and is morally oriented. Literature analysis also shows that these values have a strong conceptual fit with modern management theories, including transformational leadership, distributed leadership, and value-based leadership. Despite the challenges of integration influenced by differences in normative and pragmatic orientations, the study's findings indicate that the two paradigms can be combined to form a hybrid leadership model that is relevant to the character of Indonesian education. This research makes a theoretical contribution by offering an integrative perspective that broadens the understanding of value-based leadership, while also opening up opportunities for more empirical and practical follow-up research. Practically, the results of this study provide strategic recommendations for school leaders, educational institutions, and policymakers on developing ethical, adaptive, and contextually relevant educational governance.